Medical Ethnobiology and Ethnopharmacology in Latin America - Albuquerque, Ulysses Paulino (2012)
Through their long exposure and experience with natural resources, many local communities in Latin America have developed health care practices. Thousands of years of observation and experimentation have helped in developing different empirical medical systems, as well as knowledge of plants, animals, and minerals. Such knowledge is the subject of medical ethnobiology and ethnopharmacology, disciplines that before being exclusive actually complemented each other. In the broadest sense, both medical ethnobiology and ethnopharmacology attempt to make sense and to understand traditional medical systems: the first from perceptions, healing strategies, natural resources used to fight diseases or maintain health; the second from traditional medicines, either plants, animals, or minerals. We can find new and different types of approaches and theoretical and methodological developments such as ethnopharmacological evaluations of traditional drugs unknown so far; the inclusion of historical perspective in ethnopharmacological studies; the migration influence on traditional medical systems both in industrialized countries and remote locations, or a greater focus on urban contexts in ethnopharmacology. Moreover, the integrative aspect is noteworthy; it includesmedical ethnobotany and zootherapy (the treatment of human diseases using drug-based therapies derived from animals).